Limit pricing under third-degree price discrimination - Pires, Cesaltina (2012)
This paper shows how a multimarket incumbent can use low pre-entry prices for entry deterrence. We consider an incumbent who operates in two independent markets and has private information about his production cost. In one of the markets, there is a potential entrant offering a differentiated product. The most reasonable perfect Bayesian equilibrium is either the least-cost separating equilibrium or the pooling equilibrium where both types of incumbents set the low-cost monopoly prices. This equilibrium may involve a downward distortion in the pre-entry prices of both markets. Our model has interesting implications for antitrust regulation as well as for international trade policy. First, predatory tests based on a single market are inadequate for a multimarket incumbent. Second, a lower price in a foreign market is neither a necessary nor a sufficient condition for the existence of entry deterrence in a foreign market.